2010
DOI: 10.1111/j.1365-2311.2010.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Local host ant specificity of Phengaris (Maculinea) teleius butterfly, an obligatory social parasite of Myrmica ants

Abstract: 1. Phengaris butterflies are obligatory social parasites of Myrmica ants. Early research suggested that there is a different Myrmica host species for each of the five European Phengaris social parasites, but more recent studies have shown that this was an oversimplification.2. The pattern of host ant specificity within a Phengaris teleius metapopulation from southern Poland is reported. A combination of studying the frequency distribution of Phengaris occurrence and morphometrics on adult butterflies were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
2
30
1
1
Order By: Relevance
“…The mean patch size was 2.9 ± 0.7 ha (range: 0.005-33 ha) and the distances between neighbouring patches were usually within the range of 100-300 m (Nowicki et al 2007). These foodplant patches constitute habitat patches of P. teleius, since the aforementioned host ant species are widespread and abundant in all meadow types in our study area (Witek et al 2008(Witek et al , 2010.…”
Section: Study Species and Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The mean patch size was 2.9 ± 0.7 ha (range: 0.005-33 ha) and the distances between neighbouring patches were usually within the range of 100-300 m (Nowicki et al 2007). These foodplant patches constitute habitat patches of P. teleius, since the aforementioned host ant species are widespread and abundant in all meadow types in our study area (Witek et al 2008(Witek et al , 2010.…”
Section: Study Species and Areamentioning
confidence: 99%
“…Having reached their fourth instar, the larvae drop to the ground and are taken by the workers of Myrmica ants to their nest, where they lead a parasitic life, feeding on ant brood (Thomas et al 1998). The host ants of P. teleius are several species of Myrmica: mostly M. scabrinodis, M. rubra and M. rugulosa (Thomas et al 1989;Wynhoff et al 2008;Witek et al 2010Witek et al , 2011. The study was carried out in the vast complex of wet meadows located in the Vistula River, west of the Kraków city centre (southern Poland; Fig.…”
Section: Study Species and Areamentioning
confidence: 99%
“…To complete their life cycle they require two crucial resources, which comprise specific foodplants, on which Maculinea larvae feed in their initial stages, and specific host ants of the genus Myrmica, in the colonies of which the larvae finish their development, acting as social parasites (Thomas 1995;Witek et al 2010). There is a controversy surrounding the taxonomic status of M. alcon, with its two distinct forms associated with wet meadows and xerothermic grasslands, regarded as separate species or, more frequently, merely as different ecotypes (Als et al 2004;Pecsenye et al 2007;Sielezniew et al 2012;Bereczki et al 2018).…”
Section: Study Speciesmentioning
confidence: 99%
“…It was shown that M. scabrinodis was the most abundant Myrmica species in the metapopulation system in the Kraków region but the percentage of infested nests was similar or even lower than those of nests of M. rubra or M. ruginodis. Moreover, a decrease of infested nests of M. scabrinodis has been observed during the last 20 years (Thomas et al, 1989;Witek et al, 2010). This trend could be the consequence of the arms-race between the parasite and its host, which was also observed in other interactions between social parasites and their hosts (Lorenzi and Filippone, 2000;Foitzik et al, 2003;.…”
Section: Discussionmentioning
confidence: 92%